Evolution of [18F]fluorodeoxyglucose and [18F]fluoroazomycin arabinoside PET uptake distributions in lung tumours during radiation therapy. (3rd April 2017) - Di Perri, Dario; Lee, John A.; Bol, Anne; Hanin, François-Xavier; Janssens, Guillaume; Labar, Daniel; Robert, Annie; Sterpin, Edmond; Geets, Xavier
Abstract: Background: Dose painting (DP) aims to improve radiation therapy (RT) outcome by targeting radioresistant tumour regions identified through functional imaging, e.g., positron emission tomography (PET). Importantly, the expected benefit of DP relies on the ability of PET imaging to identify tumour areas which could be consistently targeted throughout the treatment. In this study, we analysed the spatial stability of two potential DP targets in lung cancer patients undergoing RT: the tumour burden surrogate [ 18 F]fluorodeoxyglucose (FDG) and the hypoxia surrogate [ 18 F]fluoroazomycin arabinoside (FAZA). Materials and methods: Thirteen patients with unresectable lung tumours underwent FDG and FAZA 4D-PET/CT before (pre), and during the second (w2) and third (w3) weeks of RT. All PET/CT were reconstructed in their time-averaged midposition (MidP) for further analysis. The metabolic tumour volume (MTV: FDG standardised uptake value (SUV) > 50% SUVmax ) and the hypoxic volume (HV: FAZA SUV >1.4) were delineated within the gross tumour volume (GTVCT ). The stability of FDG and FAZA PET uptake distributions during RT was subsequently assessed through volume-overlap analysis and voxel-based correlation analysis. Results: The volume-overlap analysis yielded median overlapping fraction (OF) of 0.86 between MTVpre and MTVw2 and 0.82 between MTVpre and MTVw3 . In patients with a detectable HV, median OF was 0.82 between HVpre and HVw2 and 0.90 between HVpre and HVw3 . The voxel-based correlation analysis yielded median Spearman's correlation coefficient (rS ) of 0.87 between FDGpre and FDGw2 and 0.83 between FDGpre and FDGw3 . Median rS was 0.78 between FAZApre and FAZAw2 and 0.79 between FAZApre and FAZAw3 . Conclusions: FDG and FAZA PET uptake distributions were spatially stable during the 3 first weeks of RT in patients with unresectable lung cancer, both based on volume- and voxel-based indicators. This might allow for a consistent targeting of high FDG or FAZA PET uptake regions as part of a DP strategy.